The role English plays in the economic, social, and intellectual development of teachers at Madre María Berenice School, Quito, september 2010 - Chiliquinga Arguello, Teresa del Rocío (2012)
To develop this research I have followed the scheme proposed by the Army Polytechnic School Language Department. The English language is a universal language; it helps to develop the economy, the society, and intellect of the people, the benefits of learning English are several. English language develops the economy because businessmen need to speak this language to do good business, these businesses are linked to tourism for example, tourist guides must be English speakers to guide foreign people, and it increases the number of visitors of English speakers to Ecuador. Consignments from United States help the economy; migrants have to learn English to get jobs in countries where English is spoken. English language develops the quality of life because it is a tool to get good jobs, for example; English teachers have the opportunities to get work in public institutions, and they receive a good salary, in this way the quality of life of people is getting better. Foreign people are interested in teaching English in Ecuador, to help poor societies; they teach English to children and adults, the society improves through the knowledge of a second language. Finally, students who speak English have several opportunities to get a scholarship to study in foreign Colleges where English is spoken; they are able to acquire new interesting information.